2006
DOI: 10.1074/jbc.m513900200
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of TatCd for TatAd Elucidates Its Receptor Function in the Bacillus subtilis Twin Arginine Translocation (Tat) Translocase System

Abstract: Twin arginine translocation (Tat) systems catalyze the transport of folded proteins across the bacterial cytosolic membrane or the chloroplast thylakoid membrane. In the Tat systems of Escherichia coli and many other species TatA-, TatB-, and TatClike proteins have been identified as essential translocase components. In contrast, the Bacillus subtilis phosphodiesterase PhoD-specific system consists only of a pair of TatA In bacteria, most of the exported proteins cross the cytosolic membrane through the Sec-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Two possibilities are considered: (1) TatA and TatB interact with the protein and recognize either the same or a different region of the signal peptide; (2) either TatA or TatB interacts in vivo with the Tat substrate. Very recently, it was reported that B. subtilis TatA molecules are organized as cylindermicelle-like structures with a 120 Å hydrophobic centre, which could accommodate an a-helical domain of a signal peptide (Westermann et al, 2006). As we have observed hetero-oligomerization of TatA and TatB in the cytoplasm of S. lividans, it is very likely that they are organized in similar structures.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Two possibilities are considered: (1) TatA and TatB interact with the protein and recognize either the same or a different region of the signal peptide; (2) either TatA or TatB interacts in vivo with the Tat substrate. Very recently, it was reported that B. subtilis TatA molecules are organized as cylindermicelle-like structures with a 120 Å hydrophobic centre, which could accommodate an a-helical domain of a signal peptide (Westermann et al, 2006). As we have observed hetero-oligomerization of TatA and TatB in the cytoplasm of S. lividans, it is very likely that they are organized in similar structures.…”
Section: Discussionmentioning
confidence: 62%
“…The function of TatA as being involved in pore formation and mediating transport of its Tat substrate across the cytoplasmic membrane seems to be very conserved in S. lividans, E. coli and B. subtilis. In E. coli and B. subtilis, a spectrum of TatA complexes forming ringlike structures in the membrane (Gohlke et al, 2005;Westermann et al, 2006) has been reported as well as the colocalization of Tat precursors with membrane-integrated TatA (Alami et al, 2003;Westermann et al, 2006). In addition, cross-complementation tests recently revealed that Streptomyces coelicolor TatA protein supports a high level of Tat activity in an E. coli double tatA/E mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of the co-fractionation of TatA with membranes, which depended on the hydrophobic N-terminal region of the protein, it has been assumed that TatA must be an exclusively membrane-bound component of the Tat system (35). However, electron microscopy of TatA d from Bacillus subtilis revealed that a significant portion of this TatA was present in the cytoplasm where it was able to bind the Tat substrate PhoD (8,26). The TatA d , which interacted with membranes, had substrate bound to it (9).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that it contains an N-terminal transmembrane segment (17), TatAd was also found in the cytosol, where it appears to interact with its substrate, pre-PhoD, via the signal sequence (24). TatCd was proposed to act as a receptor for the anchoring at and subsequent incorporation into the membrane of this TatAd-PhoD complex (28).…”
mentioning
confidence: 99%